2021
DOI: 10.1038/s41598-021-82232-1
|View full text |Cite
|
Sign up to set email alerts
|

Extracting sub-cycle electronic and nuclear dynamics from high harmonic spectra

Abstract: We present a new methodology for measuring few-femtosecond electronic and nuclear dynamics in both atoms and polyatomic molecules using multidimensional high harmonic generation (HHG) spectroscopy measurements, in which the spectra are recorded as a function of the laser intensity to form a two-dimensional data set. The method is applied to xenon atoms and to benzene molecules, the latter exhibiting significant fast nuclear dynamics following ionization. We uncover the signature of the sub-cycle evolution of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…From the time-resolved plasma emission (10 ps), backward re-deposition with single spot ablation likely starts about~100 ns after ablation and from the pump-probe observations, (600 fs) continues over 10 µs and longer. The debris power laws yield R deb ∝ E 0.3-0.5 for both single spot and jets but the much larger jet radii if applied to R D~f R yields f~0.7-0.8 using Equation (2) inferring that an additional energetic process is involved during the plasma plume interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the time-resolved plasma emission (10 ps), backward re-deposition with single spot ablation likely starts about~100 ns after ablation and from the pump-probe observations, (600 fs) continues over 10 µs and longer. The debris power laws yield R deb ∝ E 0.3-0.5 for both single spot and jets but the much larger jet radii if applied to R D~f R yields f~0.7-0.8 using Equation (2) inferring that an additional energetic process is involved during the plasma plume interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of intense ultrafast laser radiation with atoms, gases and solid materials has led to remarkable scientific advances such as High Harmonic Generation for attosecond spectroscopy [1,2], the use of filamentation for atmospheric probing [3,4], two-photon microscopy [5,6] and intraocular fs-LASIK in eye surgery [7]. In particular, laser ablation (LA) of materials with ps and sub-ps temporal pulse length has advanced materials analysis in areas such as Laser Ablation Inductively Coupled Mass Spectrometry (LA-ICP-MS) [8][9][10] and Laser-Induced Breakdown Spectroscopy (LIBS) [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the nuclear autocorrelation function C aa (t) (eqn (24c)) modulates the high-harmonics yield in molecules, 67 as beautifully demonstrated in PACER (''Probing attosecond dynamics by chirp-encoded recollisions'') experiments. 68,69 It has been recently shown that the shorttime autocorrelation functions can be extracted directly from the intensity-dependent HHG spectra for medium-sized molecules, 70 without resorting to elaborate theory modeling. These femtosecond nuclear dynamics in turn give access to the local potential-energy surface parameters of the transiently-created cations, 67,71 despite their fleeting, sub laser-cycle existence.…”
Section: Other Types Of Electronic Transitionsmentioning
confidence: 99%
“…While first demonstrated in smaller systems, decades of studies on strong-field rescattering and highharmonic generation (HHG) have shown that these phenomena is commonplace during strongfield processes involving polyatomic molecules. [7][8][9][10][11][12][13][14][15] Femtosecond pulses of 800 nm central wavelength and 1×10 14 W cm -2 peak intensity can tunnel ionize large polyatomic molecules with ionization potentials (IPs) ranging from 8 to 10 eV, creating high-energy electrons that can deposit much of their energy back into the molecule upon rescattering. The maximum kinetic energy of the rescattering electrons is proportional to the laser intensity, approximately 3.2 Up, 16 where Up is the ponderomotive energy.…”
Section: Introductionmentioning
confidence: 99%